Etude préliminaire de l'influence des disponibilités alimentaires et des activités humaines sur l’utilisation spatiale de l’habitat par les chimpanzés et les bonobos - Victor Narat; Marie Cibot; Jean Christophe Bokika Ngawolo; Richard Dumez; Sabrina Krief (Revue de Primatologie)
Great apes are endangered due to poaching, deforestation, habitat loss and habitat fragmentation. Studying the interactions between great apes, their environment and local population is necessary for understanding the adaptability of great apes to habitat disturbance and to assess the specific threats in the local context. Development of the human communities is expected to result from conservation strategies suggested from such studies. This preliminary study compares how food availability and human activities influence the local distribution of apes belonging to the two species of the genus Pan, chimpanzees (Pan troglodytes schweinfurthii) and bonobos (Pan paniscus). Chimpanzees and bonobos were surveyed in areas where these species are not eaten by local people respectively at Sebitoli in the Northern part of Kibale National Park in Western Uganda and at Embinima in the community conservation area of the non-governmental organization Mbou-Mon-Tour, Democratic Republic of Congo (DRC).A long term study has recently started in these two sites, associated with the establishment of a process of habituation of the ape communities studied. The study periods cover 11 months in Uganda and seven months in DRC in 2010-2011. We collected ad libitum data (direct observation and indirect signs of apes and human beings) during the habituation process. To test the influence of the human presence and the fruit availability, we used transect census (walked every 12 days) and ad libitum census. We surveyed 130 trees from 18 species in Uganda and 949 trees from 18 species in DRC.The analyses of these preliminary data provide opposite results for the two species and sites. Chimpanzee evidences were positively correlated with fruit availability along the transects, but they were not correlated with human activities evidences. On the contrary, fruit availability did not influence bonobo distribution, but there is a negative correlation between human activities and bonobo presence (only during the 2010 study period). Among human activities recorded within the home range of Sebitoli chimpanzees, poaching has high consequences on chimpanzees as they sometimes get trapped in cable snares placed to capture duikers and are deeply injured : 23 chimpanzees among 65 identified so far, suffer from mutilations due to snares (21 wire snares deactivated during the study period). Charcoal burning or fire wood collection also occur but human presence is prohibited within the National Park. Human activities in the home range of bonobos are more diversified, with several traditional activities (culture, gathering, hunting with nylon snares) and the encounter rates of human signs is higher (2,3 signs/km, 48 km) than in Uganda (1,84 signs/km, 74,5 km)In the future, increased habituation, detailed habitat characterization including spatial and phenological monitoring of Ape food, especially terrestrial herbaceous vegetation and interviews of a larger sample of local persons will allow performing a detailed spatio-temporal analysis of habitat use by bonobos and chimpanzees.Such studies may provide a better understanding of the adaptability of these species and their representation by local human communities to propose appropriate conservation strategies including improvement of local people well-being and wealth.